PTH-159 Group Education is as Effective as one-to-one Sessions when Administering the Low Fodmap Diet in Functional Bowel Disorders. (4th June 2013) - Joyce, T; Staudacher, H M; Whelan, K; Irving, P M; Lomer, M C
Abstract : Introduction: The low FODMAP diet is an effective intervention for people with functional bowel disorders (FBD). It has been introduced successfully to the UK with > 250 dietitians trained in its implementation. However, teaching patients about the diet is labour intensive; initial appointments typically last one hour. Given the prevalence of FBD, this represents a significant obstacle to widespread use. Group education sessions (GS) are a possible solution and are effective for dietary interventions in other disorders (e.g. diabetes, obesity), although their effectiveness has not been established for the low FODMAP diet. We aimed to compare the effectiveness of GS with one-to-one sessions (OS). Methods: Patients referred in 2011–12 with FBD were pre-assessed by telephone to confirm suitability for GS. Those with atypical symptoms or with other medical or nutritional concerns were excluded. Suitable patients were offered the choice of GS or OS. Up to 12 patients were seen in each GS lasting 1.5h and were then followed up 6–10 weeks later in a 1h GS. Patients seen in OS had an initial 1h appointment and then a 0.33h follow-up, 6–10 weeks later. Effectiveness of the diet was compared in OS and GS. Symptoms were measured using the gastrointestinal symptom rating scale at baseline and follow-up and clinical effectiveness through the global symptom question (GSQ). Comparisons were made using the χ2 test. Acceptability of GS sessions was also assessed. Results: Data from 168 patients attending GS (70% female, mean age 39y) were compared with 50 patients attending OS (60% female, mean age 47y). Positive responses to the GSQ 'do you currently have satisfactory relief of your gut symptoms' improved from 30/155 (19%) at baseline to 71/146 (49%) in the GS (P < 0.001) and from 2/45 (4%) to 23/44 (52%) in the OS patients (P = 0.016). Proportion of those with adequate control at follow up was not significantly different between OS and GS (P = 0.895). At follow up, 94% of GS patients reported adherence to the diet > 50% of the time. Most of the GS patients felt length of the sessions (95%), content (93%) and balance between education and patient involvement (95%) were 'just right'. In retrospect, 39% would have preferred OS, with the remainder preferring GS or expressing no preference. Conclusion: GS are an effective medium for instructing patients in the implementation of the low FODMAP diet. Whilst a significant minority attending GS would have preferred OS, there are several possible advantages to GS including peer-support and sharing of experiences. Most importantly, GS allow increased capacity and shorter waiting times. Disclosure of Interest: None Declared.